The Signification of Bronfenbrenner's Theory: An Analysis of the Developmental Ecology Approach to Holistic Value Education - Aprilianata; Sekarsari, Peni; Fauziah, Hamidah Ulfa; Marzuki (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
Value education requires a holistic approach so that values ​​can be fully internalized in the daily lives of students. One of the relevant theoretical frameworks in understanding the complexity of this process is the ecological development theory proposed by Urie Bronfenbrenner. This theory offers a comprehensive perspective by emphasizing the importance of interactions between systems in the individual's development environment. This study aims to examine the relevance of Bronfenbrenner's ecological development theory in the context of value education as a comprehensive and integrated process. The method used in this study is library research, with primary data sources in the form of Bronfenbrenner's original works, and supported by secondary sources such as books, scientific journals, and other relevant literature. Bronfenbrenner's theory states that noble values ​​such as Pancasila can become living values ​​if they are internalized through a consistent and sustainable interaction process in all levels of the environment, starting from family, school, society, to broader social and cultural policies. Therefore, a holistic approach to value education needs to consider all systemic dimensions that influence individual development. The contribution of this research is to enrich the study of educational values ​​with the integration of five ecological systems (microsystem, mesosystem, exosystem, macrosystem, and chronosystem) as interrelated dimensions in the process of internalizing values ​​and to emphasize that internalizing values ​​such as Pancasila requires the active involvement of all social environments that influence individuals, from the family to the cultural system and state policies.